Petit guide sur le cinéma des femmes - Ouellet-Cummings, Catherine (Ciné-Bulles, 2011)
Thérèse Lamartine est bien connue des milieux féministes. Détentrice d’une maîtrise en études cinématographiques, elle a publié Elles, cinéastes... ad lib, en 1985, aux Éditions Remue-ménage, dans lequel elle présentait des réalisatrices de diverses origines, actives entre 1895 et 1981. En 2009, elle publiait Soudoyer Dieu, un roman scrutant la longue et inconsolable douleur d’un groupe de femmes après la tuerie de Polytechnique. Avec Le Féminin au cinéma, une petite plaquette consacrée aux films «de femmes» ou, comme elle le précise, aux films qui «sculptent un art du mieux-vivre la mixité dans nos sociétés ou [qui] débrident les stéréotypes et nous dérident à la fois», Lamartine ouvre les portes d’un monde cinématographique souvent méconnu et rend hommage à des femmes de cinéma, autant derrière que devant la caméra. En sortant ces femmes de l’ombre, elle met au jour un cinéma riche et original, mais méconnu.
Keywords: 1-Cinéma; 2-Approches sociologiques; 2-Genre et sexualité; 2-Étude des représentations; 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice; 5-Créatrice; _Nettoyé

Embodied Female Experience Through the Lens of Imagination - Green, Sharon R. (Journal of Analytical Psychology, 2010)
In 1971, I made a film entitled Self Portrait of a Nude Model Turned Cinematographer in which I explore the objectifying ‘male’ gaze on my body in contrast to the subjective lived experience of my body. The film was a radical challenge to the gaze that objectifies woman – and thus imprisons her – which had hitherto dominated narrative cinema. Since the objectification of women has largely excluded us from the privileged phallogocentric discourses, in this paper I hope to bring into the psychoanalytic dialogue a woman's lived experience. I will approach this by exploring how remembering this film has become a personally transformative experience as I look back on it through the lens of postmodern and feminist discourses that have emerged since it was made. In addition, I will explore how this process of imaginatively looking back on an artistic creation to generate new discourses in the present is similar to the transformative process of analysis. Lastly, I will present a clinical example, where my embodied countertransference response to a patient's subjection to the objectifying male gaze opens space for a new discourse about her body to emerge.
_eprint: https://onlinelibrary.wiley.com/doi/pdf/10.1111/j.1468-5922.2010.01847.x
Keywords: 1-Cinéma; 2-Genre et sexualité; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice; _Nettoyé

Auto-histoires et représentations communautaires dans le cinéma des femmes autochtones - Bertrand, Karine (Canadian Journal of Film Studies, 2020)
In the last decade or so, cinema has revealed itself to be an ideal medium for the transfer and/or remediation of the spoken word as well as stories coming from oral tradition and Indigenous culture. Indeed, cinema is a place of expression which favours cyclical creativity and contributes to the decolonization of stereotyped images propagated by external voices that do not understand the subtleties of languages (real and symbolic) that are anchored in indigenous peoples’ cultural memory. By exploring indigenous cinema as practised by women of diverse nations, this piece demonstrates how cinema can induce the compression and dilation of time, to bring to the audience the fluidity of a story that has been reconfigured according to a new time and carried by spoken words that have chosen to either emancipate themselves from the image or to materialize themselves in it. Furthermore, this article illustrates how a new generation of Indigenous women use cinema to retrace and/or rewrite their personal narrative with the help of autobiographical or collective stories that travel back in time to fill in the blanks left by a fragile memory and to express their will to make peace with a difficult colonial past. Finally, the writings of Lee Maracle (I Am Woman, 1988) and Natasha Kanapé Fontaine (Manifeste Assi, 2014) are being brought forth to show how films such as Suckerfish (Lisa Jackson, 2004) Bithos (Elle-Máijá Tailfeathers, 2015) and Four Faces of the Moon (Amanda Strong, 2016) contribute to the individual and community healing of Indigenous peoples of Canada, through an aesthetic of reconciliation. The exploration of these works, therefore allows us to shed light on and better understand the roles/internal mechanisms of visual autobiographies in the larger context of reconciliation with individual and collective stories/memories.
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice; 5-Auteur.rice autochtone; 5-Créateur.rice PANDC; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé